-48+3m=-6(1-4m)

Simple and best practice solution for -48+3m=-6(1-4m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -48+3m=-6(1-4m) equation:


Simplifying
-48 + 3m = -6(1 + -4m)
-48 + 3m = (1 * -6 + -4m * -6)
-48 + 3m = (-6 + 24m)

Solving
-48 + 3m = -6 + 24m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-24m' to each side of the equation.
-48 + 3m + -24m = -6 + 24m + -24m

Combine like terms: 3m + -24m = -21m
-48 + -21m = -6 + 24m + -24m

Combine like terms: 24m + -24m = 0
-48 + -21m = -6 + 0
-48 + -21m = -6

Add '48' to each side of the equation.
-48 + 48 + -21m = -6 + 48

Combine like terms: -48 + 48 = 0
0 + -21m = -6 + 48
-21m = -6 + 48

Combine like terms: -6 + 48 = 42
-21m = 42

Divide each side by '-21'.
m = -2

Simplifying
m = -2

See similar equations:

| ln(4x^2-100)-ln(x-2)=0 | | -2p+3=8p-7 | | 9c-3=15c+15 | | 12h+2h-3=5h+1+h | | 2x+5x+20=3x | | (2/3)(-11/8), | | -27+20e=73 | | .05x+150=2500 | | 2z+9.75=-5.15 | | -1-3a+8a=7a-3a | | N+4n+2=-13 | | X+y+z=104 | | 7q+7q= | | x^-4/x^-9 | | 2=(1/p) | | 2x^2-18+30=0 | | 7(d-5)+12= | | 3n/4=1 | | 2x^2-18x+30=0 | | 0.3333=(1/p) | | -4+8x=100 | | 3x+2-1=47 | | lnx^2+3*lnx-4=0 | | 12=40n | | 3x-6=-14+4x | | x/-2-5=12 | | 125xy-27xy= | | w+2-3w-4+5w+6-7w-8= | | -6-3(1-2n)=45-3n | | 13x+2y=-43 | | 3x^3-24x^2=-45x | | X-1=5X+3P-8 |

Equations solver categories